Development and Preliminary Evaluation of a Patient-facing Educational Video About Live Kidney Donor Surgical Complications. Issue 9 (6th August 2021) - Smith, Sophia; Haseley, Nicole; Keller, Maria; Cadzow, Renee; Feeley, Thomas H.; Kayler, Liise K.
Abstract : Background: Living kidney donation (LKD) improves transplant access; however, its use is compromised, in part, by individuals' unaddressed concerns about perioperative complications. Methods: We developed an animated, patient-centered educational video about LKD surgical complications, with input from experts in transplantation, communication, and anthropology, 35 patients/care partners (5 LKD candidates, 5 prior LKDs, 10 kidney transplant recipients, 10 kidney transplant candidates, 5 care partners), and 1 community advocate. We then conducted an online pre-post study with 24 potential kidney donors and recipients to measure the video's acceptability and feasibility to improve donation complication knowledge and concerns. Results: Knowledge of LKD surgical complications increased 23% (mean 5.7 to 7.0, P < 0.01) from pre- to post- animation viewing. Large knowledge effect size increases were observed for different levels of age, race, health literacy, and technology access. The frequency of positive responses about donation safety increased from 88% preanimation to 96% postanimation. Concerns about surgical complications remained at 17% before and after exposure. After viewing the animation, over 90% indicated positive ratings on ease of watching, understanding, and engaging. Conclusions: An animated educational video about LKD surgical complications was developed in collaboration with multiple stakeholders. The video was well received and promised to positively impact individuals' knowledge and concerns.